Interaction of inflammatory cells and oral microorganisms. III. Modulation of rabbit polymorphonuclear leukocyte hydrolase release response to Actinomyces viscosus and Streptococcus mutans by immunoglobulins and complement. - McArthur, W P (1976)
In the absence of antiserum, rabbit polymorphonuclear leukocytes (PMNs) released lysosomal enzymes in response to Actinomyces viscosus (19246) but not to Streptococcus mutans (6715). Antibodies had a marked modulating influence on these reactions. PMN hydrolase release was significantly enhanced to both organisms when specific rabbit antiserum and isolated immunoglobulin G (IgG) were included in the incubations. Immune complex F(ab')2 fragments of IgG directed against S. mutans agglutinated bacteria. Immune complexes consisting of S. mutans and F(ab')2 fragments of IgG directed against this organism were not effective as bacteria-IgG complexes in stimulating PMN release. The intensity of the release response to bacteria-IgG complexes was also diminished when PMNs were preincubated with isolated Fc fragments derived from IgG. Fresh serum as a source of complement components had no demonstrable effect on PMN release either alone or in conjuction with antiserum in these experiments. These data may be relevant to the mechanisms and consequences of the interaction of PMNs and plaque bacteria in the pathogenesis of periodontal disease.